PENGARUH MODEL PEMBELAJARAN SAVI TERHADAP PEMAHAMAN KONSEP PECAHAN SISWA KELAS IV SDN 6 MUARA DUA - Aprilyanti, Alya; Kasturi, Dinda; Tana, Farah; Rauzah, Fitri; Kasumah; ‘Aina, Nur; Rahmalisa; Bahri, Samsul (LPPM Institut Ahmad Dahlan Probolinggo, 2025)
The research aims to determine the influence of the Somatic, Auditory, Visualization, Intellectually (SAVI) model on the ability to understand the concept of fractions of grade IV students of SDN 6 Muara Dua. This study uses a quantitative research method with an experimental design. The subject of this study is grade IV students who are divided into two groups. The experimental group was applied with the SAVI learning model and the control group followed the conventional learning method. Data was collected through a fraction concept comprehension test before and after learning. The researcher conducted a hypothesis test using a t-test. From the results of hypothesis testing using statistical formulas, a significant result of the t-test was obtained, namely 0.017, meaning 0.017 <0.05) which means accepting H1 minus H0. Based on the results of the study, it can be concluded that